Lung mast cells and hypoxic pulmonary hypertension - Maxová, H; Herget, J; Vízek, M (Physiological research, 2012)
Hypoxic pulmonary hypertension (HPH) is a syndrome characterized by the increase of pulmonary vascular tone and the structural remodeling of peripheral pulmonary arteries. Mast cells have an important role in many inflammatory diseases and they are also involved in tissue remodeling. Tissue hypoxia is associated with mast cell activation and the release of proteolytic enzymes, angiogenic and growth factors which mediate tissue destruction and remodeling in a variety of physiological and pathological conditions. Here we focused on the role of mast cells in the pathogenesis of hypoxic pulmonary hypertension from the past to the present.
Keywords: mastocyty; Mast Cells; Animals; plicní hypertenze; Cell Hypoxia; Humans; Hypertension, Pulmonary; lidé; zvířata; hypoxie buňky